1995
DOI: 10.1073/pnas.92.14.6434
|View full text |Cite
|
Sign up to set email alerts
|

Mice develop normally without the H1(0) linker histone.

Abstract: Hi histones bind to the linker DNA between nucleosome core particles and facilitate the folding of chromatin into a 30-nm fiber. Mice contain at least seven nonal-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
136
2
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(149 citation statements)
references
References 42 publications
7
136
2
3
Order By: Relevance
“…Expression of the chimeric H1 also led to recruitment of DNMT1 and DNMT3B to the H19 and Gtl2 ICRs, whereas expression of H1c and a truncated H1d lacking this region of the CTD did not lead to recruitment of the two DNMTs. Gene inactivation studies in mice have not revealed essential functions for any of these histone H1 subtypes, including H1c and H1(0) (15)(16)(17). Interestingly however, we reported previously that the genes encoding H1(0) and H1c exhibit differences in their regulation compared with the genes encoding the four other subtypes (40)(41)(42).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Expression of the chimeric H1 also led to recruitment of DNMT1 and DNMT3B to the H19 and Gtl2 ICRs, whereas expression of H1c and a truncated H1d lacking this region of the CTD did not lead to recruitment of the two DNMTs. Gene inactivation studies in mice have not revealed essential functions for any of these histone H1 subtypes, including H1c and H1(0) (15)(16)(17). Interestingly however, we reported previously that the genes encoding H1(0) and H1c exhibit differences in their regulation compared with the genes encoding the four other subtypes (40)(41)(42).…”
Section: Discussionmentioning
confidence: 93%
“…Mammals contain at least eight histone H1 subtypes or variants that differ in amino acid sequences and expression during development (12)(13)(14). Functional differences among these subtypes have been difficult to identify because they appear to act redundantly in development (14)(15)(16)(17). Although the precise location of histone H1 within the chromatin fiber is uncertain, it is known that histone H1 resides outside the nucleosome core particle, where it associates with the DNA as it enters and exits the core particle and protects an additional ∼20 bp of DNA (linker DNA).…”
mentioning
confidence: 99%
“…Nuclei and chromatin preparation, and extraction of basic NPs (BNPs) from total testes or sonication-resistant spermatids (SRS) were performed as described (20,21,27).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in a Saccharomyces cerevisiae mutant lacking one of two H2A/ H2B gene pairs, the expression of the residual pair increases to compensate for the deficiency (Osley & Hereford 1981;Moran et al 1990). In mice devoid of H1 0 , other H1 genes are transcribed more than in the wild-type mice (Sirotkin et al 1995). In three types of chicken DT40 mutants (the above-mentioned 01H1-and H2B-V-deficient mutants, and the H3-IV/H3-Vdeficient mutant), expression of the remaining five H1 genes, seven H2B genes and nine H3 genes increases to compensate for the mutations (Seguchi et al 1995;Takami et al 1995a,b).…”
Section: Introductionmentioning
confidence: 99%